Influence of Hypoxia on the Epithelial-Pathogen Interactions in the Lung: Implications for Respiratory Disease - Page, Lee K.; Staples, Karl J.; Spalluto, C. Mirella; Watson, Alastair; Wilkinson, Tom M. A. (Frontiers in Immunology, 2021)
Under normal physiological conditions, the lung remains an oxygen rich environment. However, prominent regions of hypoxia are a common feature of infected and inflamed tissues and many chronic inflammatory respiratory diseases are associated with mucosal and systemic hypoxia. The airway epithelium represents a key interface with the external environment and is the first line of defense against potentially harmful agents including respiratory pathogens. The protective arsenal of the airway epithelium is provided in the form of physical barriers, and the production of an array of antimicrobial host defense molecules, proinflammatory cytokines and chemokines, in response to activation by receptors. Dysregulation of the airway epithelial innate immune response is associated with a compromised immunity and chronic inflammation of the lung. An increasing body of evidence indicates a distinct role for hypoxia in the dysfunction of the airway epithelium and in the responses of both innate immunity and of respiratory pathogens. Here we review the current evidence around the role of tissue hypoxia in modulating the host-pathogen interaction at the airway epithelium. Furthermore, we highlight the work needed to delineate the role of tissue hypoxia in the pathophysiology of chronic inflammatory lung diseases such as asthma, cystic fibrosis, and chronic obstructive pulmonary disease in addition to novel respiratory diseases such as COVID-19. Elucidating the molecular mechanisms underlying the epithelial-pathogen interactions in the setting of hypoxia will enable better understanding of persistent infections and complex disease processes in chronic inflammatory lung diseases and may aid the identification of novel therapeutic targets and strategies.